Sediment transport on the shelf margin of the Grand Banks of Newfoundland - Barrie, J.; Collins, M. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1989)
A thin cover of sand and gravel, formed during the early Holocene transgression, covers the northeastern Grand Banks of Newfoundland in water depths of between 70 and 130 m. The sediments are presently being reworked but only during the winter months of higher wave activity. Sediment threshold under waves in 70 m water depth is exceeded over 30% of the time during the months of November to March. Net sediment transport is towards the south-southeast, parallel to the bathymctric contours. Currents required to generate the larger bedforms are known to occur only infrequently. Hence, combined wave and steady flow, often in the same direction, are the probable generating mechanism for the bedforms.